Potensi Novel Cintaku di Lembata Karya Sari Narulita sebagai Media Promosi Pariwisata Lembata - NTT - Rimalinda Lukitasari; Elsita Lisnawati Guntar; Ni Ketut Veri Kusumaningrum (JURNAL MASTER PARIWISATA, 2021)
The designing of promotional media is an important thing in supporting the development of a tourism destination. With the tight competition among the destinations, the tourist choices are swinging choices. These days, the storytelling method is a method that highly buzzed in the marketing because it is considered effective to influence the future consumen emotionally. The novel of Cintaku di Lembata is a travellougue novel which tells about a tour to Lembata Island. Seing to its many predecors that has successfully raise the popularity of the destination that being used as the setting in the novel, then the potential of this novel to become a promostional media for Lembata – NTT is also worth to be researched. The purpose of this research is to know the potential of the novel of Cintaku di Lembata as a promotional media and the strategy that can be applied to maximize its utilization. The researched was conducted qualitatively with the data collection method of observation, interview, and focus group discussion (FGD). The theory that was applied was the theory of tourism promotion and the data analysis was done by using the SWOT method. The result shows that the novel of Cintaku di Lembata is very potential to become a tourism promotional media for Lembata because the content is informative and persuasive. However, there are some adjustments needed to maximize the utilization of the novel Cintaku di Lembata to promote Lembata – NTT. Those adjustments include, among others, in the matter of transforming the form into a film form and to choose the focus of attraction to be shown. Keywords: Promotion, Destination, Storytelling, Cintaku di Lembata, NTT, SWOT